MINAT ANGGOTA KWT DALAM PENGGUNAAN Trichoderma sp. PADA BUDIDAYA CABAI (Capsicum Annum L.)DI DESA TUNGKAL I KECAMATAN TUNGKAL ILIR - Shita Syaqilla; Rudi Hartono; Ait Maryani (Jurnal Inovasi Penelitian, 2020)
Abstract The high use of chemical pesticides not only causes pest and disease resistance, but can also result in low production and can damage ecosystem. The technology recommended by the ministry of agriculture to overcome the negative effects of chemical pesticides is the application of Integrated Pest Management (IPM). One component of IPM that can overcome pathogenic attacks and is also useful as a decomposing organism is biological agents Trichoderma. This study aims to describe the interests of KWT members in their use Trichoderma, analyze related factors and determine strategies that can be done to increase the interest of KWT members in use Trichoderma. The assessment sample was a census of 32 farmers. The assessment variables are internal factors, external factors and KWT members interest in use Trichoderma. Data collection techniques in the form of interviews, questionnaires and observations. Data analysis is descriptive analysis, correlation analysis Spearman's rank and analysis Kendall's W. The results of the assessment regarding the interests of KWT members are in the medium category. Related factors are external factors. One strategy to increase farmers' interest is to actively carry out extension activities with methods, media and material about technology Trichoderma.